Potential of Siam Weed (Crhomolaena Odorata) as Fertilizer and Liquid Pesticide and Its Applications to Increase Crop Production - Jusna Ahmad; Chairunnsah J. Lamangantjo; Wirnangsi D. Uno; Ilyas H. Husain (Jurnal Biologi Tropis, 2022)
Siam weed (Chromolaena odorata) which can be used as fertilizer and vegetable pesticide in liquid form. Siamese weeds are very abundant and we can find them in almost all areas of uncultivated garden land. The purpose of this study was to determine the ability of Siamese weed (C. odorata) as fertilizer and pesticide in liquid form on the growth of horticultural crops. The type of research is experimental as well as quantitative exploratory. Analysis used a randomized block design (RAK), with four treatments and six replications, namely: Treatment K (without Siamese weed fertilizer and pesticide), treatment A (Liquid organic fertilizer for Siamese weeds 20%), treatment B (liquid organic fertilizer for weeds). siam 30 %), and treatment C (liquid organic fertilizer of weedsiam 40%), treatment D (liquid organic fertilizer of weed siam 50%), and treatment E (liquid organic fertilizer of weedsiam 60%), the results obtained were the concentration of liquid organic fertilizer (POC) Siamese weed leaves with a concentration of 60% (treatment E) had a significant effect on the growth of purple eggplant and shallot plants.